(untitled) (Archaeologia Adriatica, 2007)
During the archaeological excavations at the site of Sv. Križ (Church of the Holy Cross) in Nin in 1969, in the immediate vicinity of the church itself traces were found of a dwelling structure from the Gothic-Renaissance period. Excavations were continued in 1970, and afterwards from 1997 to 2000, when the entire site was excavated completely. A large quantity of late medieval and early modern glazed pottery was found inside the Gothic-Renaissance house. The pottery material from the period of the 14th-17th centuries included glazed vessels that belong to varied types and decorative styles of glazed pottery. The two basic kinds of glazed pottery can be found among this material: slipped pottery and majolica. Slipped pottery was represented by simple vessels covered with a colored glaze, followed by painted and engraved pottery whose decoration was produced through a technique of incision with a sharp point and blunt piece of board. Various decorative styles can be noted for this type, and engraved pottery includes the earliest archaic group from the second half of the 14th century, Renaissance pottery belonging to the 15th and 16th centuries, and late engraved pottery from the end of the 16th and first half of the 17th centuries. Varied decorative styles can also be noted among the finds of majolica. After the archaic majolica, dated to the second half of the 14th century, in the 15th and 16th centuries follow styles of Gothic and Renaissance inspiration, such as the severo or bello styles, and finds with alla porcellana, berettina, and bianco su bianco decoration, while the compendiario style characteristic for the second half of the 16th and beginning of the 17th centuries. Most of the glazed pottery material came from the Italian workshops of the Veneto and Emilia-Romagna, while only one fragment of a vessel came from Spanish majolica. Spanish majolica was the most valuable and best known type of glazed pottery from this period, and the fragment from Nin was made in the workshops of Valencia in the 15th century. All the finds of glazed pottery discovered at this site confirm the comfortable lifestyles and economic prosperity of the inhabitants of Nin, as well as the strong trade connections of this area with the other European countries.